A financial-economic evaluation of insurance guaranty fund system: An agency cost perspective - Han, Li-Ming; Lai, Gene C.; Witt, Robert C. (Journal of Banking & Finance, 1997)
Recent occurrences of financial distress to some insurers have raised questions about whether the current guaranty system is adequate to protect policyholders. Four new systems have been proposed. Using the state preference model, it was found the Stewart's national system faring the best, if it adopts uniform regulation. Based on agency theory, the pre-assessment approach and the policyholder surcharge (or premium increase) recoupment method were found to be better than the current post-assessment approach and premium tax offset method. Furthermore, uniform policy limits and regulations are recommended.